Oral Cancer Senario in Multiple Centers of Dhaka, Bangladesh - Sah, Dr. Rajesh; Akhter, Dr. Mahmuda (International Journal of Innovative Research in Medical Science, 2020)
Oral cancer is one of the common cancers worldwide and in Bangladesh around 7000 cases are diagnosed yearly. It has variable demographics and patient comes to hospital with different presentations. It is mandatory to know the characteristics of the disease so that better awareness and different treatment modalities can be planned. 162 patients with histopathological diagnosis of oral cancer was include in study by consecutive sampling and characteristics of disease was recorded in scientific data collection sheet which was later analyzed by SPSS and result was presented in table, graph and chart form. Incidence of oral cancer is 56.2% in female, in 59.9% cases buccal mucosa is involved in which 90.1% is squamous cell carcinoma. In Conclusion squamous cell carcinoma is most common oral cancer mainly occurs in buccal mucosa of female, in grade I and stage iii majority of patient present in tertiary centers of Dhaka.